Agronomic performance and weed suppression in sorghum on dense sowing - Braz, Guilherme Braga Pereira; Machado, Fellipe Goulart; Carmo, Eduardo Lima do; Rocha, Antonio Germano Carpim; Simon, Gustavo André; Ferreira, Camila Jorge Bernabé (Revista de Ciências Agroveterinárias, 2019)
The dense sowing of sorghum can influence the crop yield performance. In addition, this practice can also be used in the cultural management of weeds. This study aimed to evaluate the influence of densification on sorghum sowing, agronomic crop development, and weed suppression. The experiment was conducted in the field in the randomized complete block design. The treatments were arranged in factorial arrangement 2x2x2, adopting eight replications. The first factor consisted of two row spacings, 0,50 and 0,25 m; the second factor was composed of two populations, 180,000 and 270,000 plants ha-1; finally, the third factor corresponded to the cohabitation or not with the weeds. For sorghum, the height of plants, length and panicle mass, mass of one thousand grains, and yield were evaluated. Weeds were evaluated for density and dry mass. Row spacing and plant population influenced sorghum yield components, but they did not have effect on the yield. Weed interference during the entire development cycle of sorghum reduced its yield. The densification of plants in sorghum cultivation reduced weed density and weed dry mass.